PENGEMBANGAN MODEL ASESMEN AUTENTIK MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Jenny I.S Poerwanti (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2012)
Abstract: Developing authentic assessment model for Indonesia language subject. Purpose of this research and development was to create authentic assessment model and handbook of Indonesia language subject authentic assessment in elementary school. The research was conducted by field research for acquiring a picture of teachers’ knowledge toward authentic assessment and an application in elementary school, and also arrangement handbook of Indonesia language subject authentic assessment in elementary school. Data collection methods were questionnaire, interview, and document. Research results showed that in general, teachers were not understand and apply truly authentic assessment, authentic assessment model and handbook of authentic assessment can be continued to another advance step. Most of teachers were hoping a training and empowerment activity in planning and applying model of teaching in elementary school.Abstrak: Penelitian pengembangan ini bertujuan menghasilkan model asesmen autentik dan buku pedoman asesmen mata pelajaran Bahasa Indonesia di Sekolah Dasar (SD). Penelitian dilakukan melalaui studi lapangan untuk memperoleh gambaran pengetahuan guru tentang asesmen autentik dan penerapannya di SD’ serta penyusunan buku pedoman asesmen autentik Bahasa Indonesia di SD. Pengumpulan data menggunakan kuisioner, wawancara, dan dokumen. Hasil penelitian menunjukkan bawa pada umumnya guru-guru belum memahami dan belum menerapkan asesmen autentik dengan benar, model asesmen autentik dan buku pedoman asesmen autentik dapat dilanjutkan ke tahap evaluasi selanjutnya, Sebahagian besar guru-guru mengharapkan kegiatan latihan dan pendampingan, dalam merancang dan menerapkan model dalam pembelajaran di SD